European ageing research in the social, behavioural and health areas: a multidimensional account - Wahl, Hans-Werner; Deeg, Dorly; Litwin, Howard (European journal of ageing, 2013)
At the 10th anniversary of the European Journal of Ageing in 2013, this article makes an attempt towards a comprehensive overview of European ageing research (EAR) from the three perspectives of this Journal: the social, behavioural and health related domains. First, we provide some general observations on the state of EAR, noting the difficulties of defining this field. Second, we provide a description of EAR and its current trends and characteristics in terms of research themes and eoretical directions. Towards this end, we use the 10 volumes of the European Journal of Ageing as well as other available information. Third, we address the infrastructure of EAR as reflected in major studies, looking at data availability, language, education and training. Given this background, we derive a set of six recommendations to further consolidate and expand EAR.
Gesehen am 23.09.2021